Aptamer Nanomaterials for Ovarian Cancer Target Theranostics - Zhao, Jing; Tan, Wenxi; Zheng, Jingying; Su, Yuanzhen; Cui, Manhua (Frontiers in Bioengineering and Biotechnology, 2022)
Ovarian cancer is among the leading causes of gynecological cancer-related mortality worldwide. Early and accurate diagnosis and an effective treatment strategy are the two primary means of improving the prognosis of patients with ovarian cancer. The development of targeted nanomaterials provides a potentially efficient strategy for ovarian cancer theranostics. Aptamer nanomaterials have emerged as promising nanoplatforms for accurate ovarian cancer diagnosis by recognizing relevant biomarkers in the serum and/or on the surface of tumor cells, as well as for effective ovarian cancer inhibition via target protein blockade on tumor cells and targeted delivery of various therapeutic agents. In this review, we summarize recent advances in aptamer nanomaterials as targeted theranostic platforms for ovarian cancer and discusses the challenges and opportunities for their clinical application. The information presented in this review represents a valuable reference for creation of a new generation of aptamer nanomaterials for use in the precise detection and treatment of ovarian cancer.